PENERAPAN PRINSIP NON DISKRIMINASI DALAM PERDAGANGAN INTERNASIONAL TERHADAP PRODUK SEJENIS DALAM SISTEM WORLD TRADE ORGANIZATION (STUDI KASUS DS406 = CLOVE CIGARETTE) - Constantin Dwi Rendragraha (BELLI AC PACIS, 2020)
This paper aims to determine the concepts of most favoured nation (MFN) and national treatment (NT) in the World Trade Organization (WTO) system and its application in the case of DS406: Clove Cigarette. The method of research, normative descriptive by using secondary data analyzed with a qualitative approach, resulting in a presentation of descriptive data and analysis. MFN and NT are a principle of non-discrimination contained in WTO. MFN is a principle that should not differentiate the treatment of WTO member States, while NT is a principle that should treatment no less favourable to local domestic products and member State products. The application of the principle to the case DS406: Clove cigarette, Panel interpretation of like product in article 2.1 TBT Agreement emphasizes that menthol cigarette product is considered to be like product of Kretek cigarette products based on the policy objectives of the Technical regulation while Appellate Body is based on competitive relationship